Membuat Konten Lingkungan Hidup di Media Sosial Untuk Mengembangkan Potensi Wisata Pulo Geulis Kota Bogor - Khotimah, Wininda Qusnul; Agustini, Vilya Dwi (Prisani Cendekia, 2023)
Content about the environment in the media is the way to educate the community about how to protect the surrounding environment. Especially for areas that have tourism potential, without the support of awareness of maintaining environmental cleanliners will certainly reduce the interest of tourist area. This traning is carried out offline by providing material, discussion and question and answer. This training went wll without experiencing any problems, the training participans gave positive feedback if a similar training was held back in their area. For the next activity, more information about photography, videography or storytelling can be given which will help in creating environmental content.